PENGARUH PENAMBAHAN MAPE PADA PROSES PEMBUATAN KOMPOSIT BERBASIS SEKAM PADI DAN BENTONIT ALAM (The Effect of MAPE Addition on Formation Process of Rice Husk and Natural Bentonite Based Composite) - Mulana, Farid; Fathanah, Umi; Syarifuddin, Syarifuddin (Jurnal Hasil Penelitian Industri, 2014)
Rice husk and natural bentonite as well as virgin HDPE were used as rawmaterials to form composite. The aim of study is to know the effect of rice husk and naturalbentonite ratio as filler and the percentage of polyethylene-graft-maleic anhydride(MAPE) as coupling agent on quality of formed composites. The composite formationprocess was done by application of hot press method at 170 oC for 30 minutes. Afterheated and pressed then composites was cooled to room temperature and finallycomposites were tested its mechanical properties of tensile strength and bending strength.The results showed that addition of natural bentonite into matrix of rice husk can increasemechanical properties of composite compared to composites prepared by using only ricehusk and virgin HDPE. The amount of added MAPE affect values of tensile and bendingstrength of composites. The addition of MAPE and natural bentonite on formation ofcomposites caused the increasing adhesion bond between matrix and filler and as a resultalso increased the mechanical properties of composites. On ratio ofrice husk and naturalbentonite of 70:30 with addition of 5 wt% MAPE was obtained the highest tensile strengthvalue of 18.2 MPa and the highest bending strength value of 9.2 MPa.